Positive electrode material and preparation method thereof, positive electrode plate, secondary battery and electric device
Patent Information
- Application Number
- CN202310749065.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-25
AI Technical Summary
Secondary batteries using nickel-containing positive electrode materials have problems with deterioration in cycle life, which is mainly due to the residual lithium element, which leads to oxygen dissolution and side reactions, which affects the stability and safety of the battery structure.
Two cladding layers are formed on the inner core surface of the lithium nickel-cobalt metal composite oxide. The first cladding layer is composed of lithium elements and X elements (fluorine, chlorine, bromine, etc.), and the second cladding layer is composed of Z elements (iron, It consists of titanium, aluminum, zinc, magnesium, etc.), and a uniform protective film is formed through the salts of these elements, reducing oxygen dissolution and side reactions.
The cycle stability of lithium nickel-cobalt metal composite oxide and the cycle life of secondary batteries are improved, and the safety of the battery is enhanced.
Smart Images

Figure CN119208586A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device. Background Art
[0002] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features such as light weight, no pollution, and no memory effect. With the development of secondary battery technology, people have higher and higher requirements for the energy density of secondary batteries. In order to improve the energy density of batteries, nickel-containing positive electrode materials are often used. However, in the related art, secondary batteries using nickel-containing positive electrode materials have the problem of deteriorating cycle life. Summary of the invention
[0003] Based on this, it is necessary to provide a positive electrode material and a preparation method thereof, a positive electrode plate, a secondary battery and an electrical device to improve the cycle life and safety of the secondary battery.
[0004] In order to achieve the above-mentioned object, the first aspect of the present application provides a positive electrode material, comprising:
[0005] A core, wherein the material of the core comprises a lithium nickel cobalt metal composite oxide; in the lithium nickel cobalt metal composite oxide, the molar proportion of nickel element in the total metal elements other than lithium element is 30%-95%;
[0006] A first coating layer, coated on at least a portion of the outer surface of the core, wherein the material of the first coating layer includes lithium element and X element; and
[0007] A second coating layer, coating at least a portion of the outer surface of the core having the first coating layer, wherein the material of the second coating layer includes an X element and a Z element;
[0008] The X element includes one or more of fluorine, chlorine and bromine, and the Z element includes one or more of iron, titanium, aluminum, zinc and magnesium.
[0009] The positive electrode material of the present application can eliminate residual lithium on the surface of the core by forming a first coating layer containing lithium and X elements on at least part of the surface of the core. At the same time, the first coating layer has a high oxygen vacancy formation energy, which can reduce or even avoid oxygen dissolution inside the core, which is beneficial to improve the structural stability of the core during the cycle process, reduce or even avoid the side reaction between oxygen and the electrolyte caused by oxygen dissolution, and improve the cycle life and safety of the secondary battery. By forming a second coating layer on at least part of the surface of the core with the first coating layer, the problem of uneven coating of the first coating layer that may be caused by low residual lithium on the surface of the core can be reduced or even avoided, and a uniform protective film is formed on the surface of the first coating layer to reduce or even avoid oxygen overflow from the position not coated with the first coating layer.
[0010] In some embodiments, the second coating layer is coated on the entire outer surface of the inner core having the first coating layer.
[0011] In some embodiments, the lithium nickel cobalt metal composite oxide has a structural formula of Li x (Ni a Co b Mn c ) 1-d M d O 2- y A y , wherein 0.2≤x≤1.2, a+b+c=1, the M element includes one or more of Al, Mg, Zr, W, Ti and Y, and the A element includes one or more of B, P and F.
[0012] In some embodiments, the first coating layer has at least one of the following features:
[0013] (1) The mass percentage of the lithium element contained in the first coating layer to the positive electrode material is 0.1%-0.3%;
[0014] (2) The material of the first coating layer includes a salt containing both the lithium element and the X element;
[0015] (3) The thickness of the first coating layer is 3nm-10nm.
[0016] In some embodiments, the second coating layer has at least one of the following features:
[0017] (1) The mass percentage of the Z element contained in the second coating layer to the positive electrode material is 0.2%-0.6%;
[0018] (2) the material of the second coating layer includes a salt containing both the Z element and the X element;
[0019] (3) The thickness of the second coating layer is 5nm-10nm.
[0020] The second aspect of the present application provides a method for preparing the positive electrode material of the first aspect of the present application, comprising the following steps:
[0021] Dispersing the core in a solvent, adding a precursor containing the element X at 40° C. to 70° C., and performing a first reaction to prepare the first coating layer on at least a portion of the surface of the core;
[0022] A precursor containing the Z element is added to the reaction solution of the first reaction at 40° C.-70° C. to carry out a second reaction, so as to prepare the second coating layer on at least a portion of the surface of the core having the first coating layer.
[0023] In some embodiments, the first reaction comprises at least one of the following conditions:
[0024] (1) The precursor containing the element X includes an acidic salt containing the element X;
[0025] Optionally, the precursor containing element X includes one or more of ammonium fluoride, ammonium chloride and ammonium bromide;
[0026] (2) The molar ratio of the X element contained in the X element precursor to the lithium element remaining on the surface of the core is (1.5-6):1; optionally (2-4):1; more preferably 3:1;
[0027] (3) After adding the precursor containing the element X, the reaction time is 20 min to 40 min;
[0028] (4) The solvent includes a fatty alcohol;
[0029] Optionally, the solvent includes one or more of ethanol, ethylene glycol, propanol, butanol and butanediol.
[0030] In some embodiments, the second reaction comprises at least one of the following conditions:
[0031] (1) The Z-containing precursor includes one or more of nitrates, carbonates, sulfates and sulfites containing the Z element; the Z element includes one or more of iron, titanium, aluminum, zinc and magnesium;
[0032] (2) The molar ratio of the Z element contained in the Z element-containing precursor to the lithium element remaining on the surface of the core is (0.125-2.5):1; can be (0.25-1.5):1; more preferably 0.66:1;
[0033] (3) After adding the Z-containing precursor, the reaction time is 20 min to 40 min.
[0034] In some embodiments, the preparation method further comprises the following steps:
[0035] The reaction liquid obtained by the second reaction is filtered, the filter residue is dried, and the filter residue is subjected to a heat treatment under a protective atmosphere to prepare the positive electrode material.
[0036] In some embodiments, the heat treatment includes at least one of the following conditions:
[0037] (1) The protective gas used includes one or more of nitrogen and inert gas;
[0038] Optionally, the protective gas used includes one or more of nitrogen and argon;
[0039] (2) The reaction temperature is 300°C-400°C and the reaction time is 3h-5h.
[0040] The third aspect of the present application provides a positive electrode sheet, comprising:
[0041] A positive electrode current collector; and
[0042] The positive electrode active material layer is located on at least one side of the positive electrode current collector, and the positive electrode active material layer includes the positive electrode material of the first aspect of the present application.
[0043] The fourth aspect of the present application provides a secondary battery, comprising the positive electrode sheet of the third aspect of the present application.
[0044] A fifth aspect of the present application provides an electrical device, comprising the secondary battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0046] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0047] Figure 3 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0048] Description of reference numerals:
[0049] 1 secondary battery; 11 housing; 12 electrode assembly; 13 cover plate; 2 power-consuming device. DETAILED DESCRIPTION
[0050] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0052] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0053] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0054] In this application, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 10-1000nm means that the units of the left endpoint "10" and the right endpoint "1000" are both nm (nanometers).
[0055] In this application, "multiple", "multiple", "multiple times" and the like, unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "multiple" means greater than or equal to two. Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and similarly, any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, each separately disclosed point or single value itself can be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unambiguous range.
[0056] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values.
[0057] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.
[0058] In the related art, secondary batteries using nickel-containing positive electrode materials have the problem of deteriorated cycle life. Through research, technicians have found that during the preparation process of nickel-containing positive electrode materials, lithium-containing compounds, such as lithium oxide, lithium hydroxide or lithium salt, are easily left on the surface of the material. The lithium-containing compounds are mainly concentrated on the surface of the nickel-containing positive electrode material particles, affecting the electronic conductivity of the nickel-containing positive electrode material and causing greater polarization during the battery cycle. At the same time, the lithium-containing compounds will also react with the electrolyte, causing the consumption of effective ingredients in the electrolyte, thereby deteriorating the battery cycle life. In addition, the lithium carbonate on the surface of the nickel-containing positive electrode material particles will also cause severe flatulence at high temperatures, causing the internal pressure of the battery cell to increase, causing safety problems.
[0059] During the research process, the technicians also found that the charging process of nickel-containing positive electrode materials is accompanied by the release of lithium ions. 4+ The content gradually increased due to Ni 4+ Easy to be reduced, easy to produce Ni 4+ →Ni 3+ In order to maintain electrical neutrality, oxygen will be released in the nickel-containing positive electrode material to form oxygen vacancies. The existence of oxygen vacancies makes the transition metal elements in the nickel-containing positive electrode material more likely to shift, resulting in irreversible changes in the crystal structure of the nickel-containing positive electrode material, thereby affecting its electrical performance; in addition, the dissolved oxygen will further react with the electrolyte and accelerate the occurrence of side reactions inside the battery cell, which will not only deteriorate the electrical performance of the battery cell, but also lead to a decrease in the safety performance of the battery cell.
[0060] Based on the above problems, the present application prepares a first coating layer on at least part of the outer surface of the inner core, and prepares a second coating layer on at least part of the outer surface of the inner core having the first coating layer, so as to reduce or even avoid oxygen dissolution inside the inner core, which is beneficial to improving the structural stability of the inner core during the cycle process, reducing or even avoiding side reactions between oxygen and the electrolyte, and improving the cycle life and safety of the secondary battery.
[0061] The first aspect of the present application provides a positive electrode material, comprising: a core, a first coating layer coated on at least a portion of the outer surface of the core, and a second coating layer coated on at least a portion of the outer surface of the core having the first coating layer; the material of the core comprises a lithium nickel cobalt metal composite oxide, in which the molar proportion of nickel element in the total metal elements other than lithium element is 30%-95%; the material of the first coating layer comprises lithium element and X element; the material of the second coating layer comprises X element and Z element; the X element comprises one or more of fluorine element, chlorine element and bromine element, and the Z element comprises one or more of iron element, titanium element, aluminum element, zinc element and magnesium element.
[0062] In the lithium nickel cobalt metal composite oxide, the molar proportion of nickel in the total metal elements other than lithium is 30%-95%. As an example, in the lithium nickel cobalt metal composite oxide, the molar proportion of nickel in the total metal elements other than lithium can be but not limited to 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or the range between any two of the above values.
[0063] As an example, in the above-mentioned lithium nickel cobalt metal composite oxide, the molar proportion of nickel in the total metal elements other than lithium can be determined by the following method: using inductively coupled plasma atomic emission spectroscopy, the mass percentages of nickel, cobalt, manganese and doped metal elements in the lithium nickel cobalt metal composite oxide are obtained respectively, and the molar ratio between each metal element is obtained after conversion, and normalized, and the molar proportion of nickel in the total metal elements other than lithium is calculated.
[0064] It should be noted that the first coating layer can be coated on part of the outer surface of the core, or can completely coat the outer surface of the core, and the coating degree of the core by the first coating layer is related to the amount of lithium-containing compound remaining on the surface of the core. The second coating layer can be coated on part of the outer surface of the core having the first coating layer, or can completely coat the outer surface of the core having the first coating layer.
[0065] It should be noted that the specific type of the X element contained in the first coating layer and the specific type of the X element contained in the second coating layer may be the same or different.
[0066] It can be understood that by forming a first coating layer containing lithium and X elements on at least part of the surface of the core, the residual lithium on the surface of the core can be eliminated. At the same time, the first coating layer has a high oxygen vacancy formation energy, which can reduce or even avoid the dissolution of oxygen inside the core, which is beneficial to improve the structural stability of the core during the cycle, reduce or even avoid the side reaction between oxygen and the electrolyte caused by oxygen dissolution, and improve the cycle life and safety of the secondary battery. By forming a second coating layer on at least part of the outer surface of the core having the first coating layer, the problem of uneven coating of the first coating layer that may be caused by low residual lithium on the surface of the core can be reduced or even avoided, and a uniform protective film is formed on the surface of the first coating layer to reduce or even avoid the overflow of oxygen from the position not coated with the first coating layer.
[0067] As a possible implementation, the first coating layer is coated on the entire outer surface of the inner core, which can greatly reduce the probability of oxygen dissolution inside the inner core.
[0068] In some possible embodiments, the second coating layer is coated on the entire outer surface of the inner core having the first coating layer; the second coating layer evenly covers the surface of the material to form a film-like coating, which can further prevent oxygen from overflowing from the uncoated position on the surface of the inner core, resulting in better results.
[0069] In some embodiments, the lithium nickel cobalt metal composite oxide has the structural formula Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y , wherein 0.2≤x≤1.2, a+b+c=1, the M element includes one or more of Al, Mg, Zr, W, Ti and Y, and the A element includes one or more of B, P and F.
[0070] It should be noted that the charging and discharging process of secondary batteries is accompanied by the deintercalation and consumption of lithium ions. The molar content of lithium ions in secondary batteries is different when they are discharged to different states. The above x value range includes the molar content of lithium elements in different charging and discharging states when the secondary battery is at a voltage of 2V-5V.
[0071] In some embodiments, the mass percentage of lithium contained in the first coating layer to the positive electrode material is 0.1%-0.3%; when the mass percentage of lithium contained in the first coating layer to the positive electrode material is within the above range, the residual lithium on the surface of the inner core can be fully converted into the coating product, and the side reaction caused by the residual lithium can be reduced. As an example, the mass percentage of lithium contained in the first coating layer to the positive electrode material can be but not limited to 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3% or the range between any two of the above values.
[0072] As an example, the mass percentage of lithium contained in the first coating layer mentioned above in the positive electrode material can be determined by the following method: the type and content of the X element and the Z element contained in the coating layer are determined by ion chromatography, and the portion of the X element used to form a compound with the Z element is deducted, and the remaining portion X is used to form the first coating layer together with the lithium element. Based on the mass of the remaining portion of the X element, the mass of the lithium element contained in the first coating layer can be calculated, and then the mass percentage of the lithium element contained in the first coating layer in the positive electrode material is calculated.
[0073] In some embodiments, the material of the first coating layer includes a salt containing both lithium and element X; element X includes one or more of fluorine, chlorine, and bromine, and the material of the first coating layer includes one or more of LiF, LiCl, and LiBr.
[0074] As an example, the composition of the first coating layer material mentioned above can be determined by the following method: the types of X element and Z element contained in the coating layer are determined by ion chromatography, and then it can be determined that the composition of the first coating layer material includes a salt formed by lithium element and X element.
[0075] In some embodiments, the thickness of the first coating layer is 3nm-10nm. When the thickness of the first coating layer is within the above range, the residual lithium on the surface of the core can be removed to a large extent. As an example, the thickness of the first coating layer can be, but is not limited to, 3nm, 3.5nm, 4nm, 4.5nm, 5nm, 5.5nm, 6nm, 6.5nm, 7nm, 7.5nm, 8nm, 8.5nm, 9nm, 9.5nm, 10nm or a range between any two of the above values.
[0076] As an example, the thickness of the first coating layer can be measured by the following method: a transmission electron microscope is used to perform a phase analysis on the surface of the positive electrode material, and the thickness information of the first coating layer is simultaneously obtained.
[0077] In some embodiments, the mass percentage of Z element contained in the second coating layer to the positive electrode material is 0.2%-0.6%. When the mass percentage of Z element contained in the second coating layer to the positive electrode material is within the above range, a uniform second coating layer can be formed, and the surface area that the first coating layer fails to cover can be filled and coated to prevent the electrolyte from directly contacting the surface of the ternary material. As an example, the mass percentage of Z element contained in the second coating layer to the positive electrode material can be, but is not limited to, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6% or a range between any two of the above values.
[0078] As an example, the mass percentage of the Z element contained in the second coating layer mentioned above in the positive electrode material can be determined by the following method: the types and contents of the X and Z elements contained in the coating layer are determined by ion chromatography, and the mass percentage of the Z element in the positive electrode material is further calculated.
[0079] As a possible implementation manner, the material of the second coating layer includes a salt containing both the Z element and the X element; the Z element includes one or more of the iron element, the titanium element, the aluminum element, the zinc element and the magnesium element, the X element includes one or more of the fluorine element, the chlorine element and the bromine element, and the material of the second coating layer includes one or more of iron fluoride, titanium fluoride, aluminum fluoride, zinc fluoride, magnesium fluoride, iron chloride, titanium chloride, aluminum chloride, zinc chloride, magnesium chloride, iron bromide, titanium bromide, aluminum bromide, zinc bromide and magnesium bromide.
[0080] As an example, the composition of the second coating layer material mentioned above can be determined by the following method: the types of X element and Z element contained in the coating layer are determined by ion chromatography, and the salt formed by Z element and X element in the second coating layer can be further determined.
[0081] In some embodiments, the thickness of the second coating layer is 5nm-10nm; when the thickness of the second coating layer is within the above range, a uniform second coating layer can be formed, and the surface area that the first coating layer fails to cover can be filled and coated to prevent the electrolyte from directly contacting the surface of the ternary material. As an example, the thickness of the second coating layer can be, but is not limited to, 5nm, 5.5nm, 6nm, 6.5nm, 7nm, 7.5nm, 8nm, 8.5nm, 9nm, 9.5nm, 10nm, or a range between any two of the above values.
[0082] As an example, the thickness of the second coating layer mentioned above can be measured by the following method: using a transmission electron microscope to perform phase analysis on the surface of the positive electrode material and simultaneously obtain the thickness information of the second coating layer.
[0083] In some embodiments, the cathode material comprises:
[0084] The core material includes lithium nickel cobalt metal composite oxide; in the lithium nickel cobalt metal composite oxide, the molar proportion of nickel element in the total metal elements other than lithium element is 30%-95%; the structural formula of the lithium nickel cobalt metal composite oxide is Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y , wherein 0.2≤x≤1.2, the M element includes one or more of Al, Mg, Zr, W, Ti and Y, and the A element includes one or more of B, P and F;
[0085] A first coating layer is coated on at least part of the outer surface of the core, wherein the material of the first coating layer includes lithium and X element, wherein X element includes one or more of fluorine, chlorine and bromine; the mass percentage of lithium contained in the first coating layer to the positive electrode material is 0.1%-0.3%; the thickness of the first coating layer is 3nm-10nm; and
[0086] A second coating layer is coated on at least a portion of the outer surface of the first coating layer, wherein the material of the second coating layer includes X element and Z element, wherein Z element includes one or more of iron element, titanium element, aluminum element, zinc element and magnesium element; the mass percentage of Z element contained in the second coating layer to the positive electrode material is 0.2%-0.6%; and the thickness of the second coating layer is 5nm-10nm.
[0087] The second aspect of the present application provides a method for preparing the positive electrode material of the first aspect of the present application, comprising the following steps:
[0088] Dispersing the core in a solvent, adding a precursor containing the X element at 40° C. to 70° C., performing a first reaction, and preparing a first coating layer on at least a portion of the surface of the core;
[0089] A precursor containing the Z element is added to the reaction solution of the first reaction at 40° C.-70° C. to carry out a second reaction, so as to prepare a second coating layer on at least a portion of the surface of the core having the first coating layer.
[0090] The positive electrode material preparation method of the present application performs in-situ coating treatment on the surface of the inner core at a relatively low temperature to consume the lithium-containing compounds remaining on the surface of the inner core. At the same time, since the generated coating layer has a high oxygen vacancy formation energy, it can prevent oxygen dissolution from the inner core.
[0091] During the preparation process, first, a precursor containing the X element reacts with the lithium-containing compound remaining on the surface of the inner core to form a salt containing both the lithium element and the X element, which is coated on the outer surface of the inner core as a first coating layer; then a precursor containing the Z element is added to the reaction solution, so that the Z element reacts with the excess X element to form a salt containing both the Z element and the X element, which is coated on the outer surface of the inner core having the first coating layer as a second coating layer.
[0092] In some embodiments, the precursor containing element X used in the first reaction includes an acidic salt containing element X; since the lithium-containing compound remaining on the surface of the inner core is alkaline, the addition of the acidic precursor containing element X can cause a neutralization reaction with the lithium-containing compound to consume the residual lithium.
[0093] In some embodiments, the X-element-containing precursor used in the first reaction includes one or more of ammonium fluoride, ammonium chloride, and ammonium bromide.
[0094] In some embodiments, the molar ratio of the X element contained in the precursor containing the X element to the lithium element remaining on the surface of the core is (1.5-6):1; when the molar ratio of the X element contained in the precursor containing the X element to the lithium element remaining on the surface of the core is within the above range, the consumption effect of the residual lithium on the surface of the core is better. As an example, the molar ratio of the X element contained in the precursor containing the X element to the lithium element remaining on the surface of the core can be but is not limited to 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1 or the range between any two of the above ratios. Optionally, the molar ratio of the X element contained in the precursor containing the X element to the lithium element remaining on the surface of the core is (2-4):1. Further optionally, the molar ratio of the X element contained in the precursor containing the X element to the lithium element remaining on the surface of the core is 3:1.
[0095] As a possible implementation manner, after adding the precursor containing the element X, the reaction time is 20 min-40 min; for example, it can be but not limited to 20 min, 25 min, 30 min, 35 min, 40 min or a range between any two of the above values.
[0096] In some embodiments, the solvent of the first reaction includes a fatty alcohol; alternatively, the solvent of the first reaction includes one or more of ethanol, ethylene glycol, propanol, butanol and butanediol.
[0097] In some embodiments, the precursor containing the Z element in the second reaction includes one or more of nitrates, carbonates, sulfates and sulfites containing the Z element; the Z element includes one or more of iron, titanium, aluminum, zinc and magnesium.
[0098] In some embodiments, the molar ratio of the Z element contained in the precursor containing the Z element in the second reaction to the lithium element remaining on the surface of the inner core is (0.125-2.5): 1. When the molar ratio of the Z element contained in the precursor containing the Z element in the second reaction to the lithium element remaining on the surface of the inner core is within the above range, the excess precursor containing the X element may be consumed. As an example, the molar ratio of the Z element contained in the precursor containing the Z element in the second reaction to the lithium element remaining on the surface of the inner core can be, but is not limited to, 0.125:1, 0.15:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1 or a range between any two of the above ratios.
[0099] In some possible implementations, the molar ratio of the Z element contained in the Z element-containing precursor in the second reaction to the lithium element remaining on the surface of the inner core is (0.25-1.5):1.
[0100] In some possible implementations, in the second reaction, the molar ratio of the Z element contained in the Z element-containing precursor to the lithium element remaining on the surface of the inner core is 0.66:1.
[0101] In some embodiments, after adding the precursor containing the Z element, the reaction time is 20 min-40 min; for example, it can be but is not limited to 20 min, 25 min, 30 min, 35 min, 40 min or a range between any two of the above values.
[0102] In some embodiments, the method for preparing the positive electrode material further comprises the following steps:
[0103] The reaction liquid obtained by the second reaction is filtered, the filter residue is dried, and the filter residue is subjected to heat treatment under a protective atmosphere to prepare a positive electrode material.
[0104] By heating the coating layer, the coating strength can be enhanced, making it difficult for the coating layer to fall off.
[0105] In some embodiments, the protective gas used in the heat treatment includes one or more of nitrogen and an inert gas. Alternatively, the protective gas used in the heat treatment includes one or more of nitrogen and argon.
[0106] In some embodiments, the reaction temperature of the heating treatment is 300°C-400°C; for example, it can be but not limited to 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C or the range between any two of the above values. The reaction time of the heating treatment is 3h-5h; for example, it can be 3h, 3.5h, 4h, 4.5h, 5h or the range between any two of the above values.
[0107] In some embodiments, the method for preparing the positive electrode material comprises the following steps:
[0108] The core is dispersed in a solvent, and then a precursor containing an element X is slowly added in a water bath at 40° C. to 70° C. to perform a first reaction, so as to prepare a first coating layer on at least a portion of the surface of the core; wherein the precursor containing the element X comprises one or more of ammonium fluoride, ammonium chloride and ammonium bromide; the molar ratio of the element X contained in the precursor containing the element X to the lithium element remaining on the surface of the core is (1.5-6):1; the reaction time after adding the precursor containing the element X is 20 min to 40 min; the solvent for the first reaction comprises a fatty alcohol;
[0109] Slowly add a precursor containing the Z element to the reaction liquid of the first reaction under a water bath condition of 40°C-70°C, carry out a second reaction, and prepare a second coating layer on at least a portion of the surface of the inner core having the first coating layer; wherein the precursor containing the Z element includes one or more of nitrates, carbonates, sulfates and sulfites containing the Z element, and the Z element includes one or more of iron, titanium, aluminum, zinc and magnesium; the molar ratio of the Z element contained in the precursor containing the Z element to the lithium element remaining on the surface of the inner core is (0.125-2.5):1; the reaction time after adding the precursor containing the Z element is 20min-40min.
[0110] The third aspect of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material of the first aspect of the present application. The positive electrode plate prepared using the above positive electrode material has a longer cycle life and higher safety.
[0111] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0112] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc. The polymer material substrate includes but is not limited to one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0113] In some embodiments, the lithium-ion positive electrode active material may also include positive electrode active materials for batteries that are well known in the art. As an example, the positive electrode active material may also include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with olivine structure may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. The weight ratio of the positive electrode active material in the positive electrode film layer is 80-100% by weight, based on the total weight of the positive electrode film layer.
[0114] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode film layer is 0-20% by weight, based on the total weight of the positive electrode film layer.
[0115] In some embodiments, the positive electrode film layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0-20% by weight, based on the total weight of the positive electrode film layer.
[0116] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, wherein the positive electrode slurry has a solid content of 40-80wt%, and the viscosity at room temperature is adjusted to 5000-25000mPa·s, and the positive electrode slurry is coated on both sides of the positive electrode collector, and after drying, the positive electrode sheet is formed by cold rolling; the unit surface density of the positive electrode powder coated on one side is 12-20mg / cm 2 The compaction density of the positive electrode is 3.0-3.75g / cm 3 , optional: 3.4-3.65g / cm 3 The calculation formula of the compacted density is:
[0117] Compacted density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).
[0118] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0119] Negative electrode
[0120] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0121] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0122] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc., and the polymer material substrate includes but is not limited to polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and other substrates.
[0123] In some embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The weight ratio of the negative electrode active material in the negative electrode film layer is 70-100% by weight, based on the total weight of the negative electrode film layer.
[0124] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode film layer is 0-30% by weight, based on the total weight of the negative electrode film layer.
[0125] In some embodiments, the negative electrode film layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode film layer is 0-20 weight %, based on the total weight of the negative electrode film layer.
[0126] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)), etc. The weight ratio of the other additives in the negative electrode film layer is 0-15% by weight, based on the total weight of the negative electrode film layer.
[0127] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry, wherein the solid content of the negative electrode slurry is 30-70wt%, and the viscosity at room temperature is adjusted to 2000-10000mPa·s; the obtained negative electrode slurry is coated on the surfaces of both sides of the negative electrode current collector, and after a drying process, cold pressing such as a roller is performed to obtain a negative electrode sheet. The unit surface density of the negative electrode powder coated on one side is 7-13mg / cm 2 , the compaction density of negative electrode is 1.2-2.0g / m 3 .
[0128] Electrolytes
[0129] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0130] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0131] In some embodiments, the electrolyte salt may be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte salt is generally 0.5-5 mol / L.
[0132] In some embodiments, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0133] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0134] Isolation film
[0135] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0136] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0137] In some embodiments, the isolation film has a thickness of 3-20 μm, and optionally 5-12 μm.
[0138] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by a winding process or a lamination process; and the electrode assembly and the electrolyte are packaged using the battery cell packaging material of the first aspect of the present application.
[0139] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 1 is a square structure as an example.
[0140] In some embodiments, reference Figure 2 The outer package may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity.
[0141] The positive electrode sheet, the negative electrode sheet and the separator can be wound or laminated to form an electrode assembly 12. The electrode assembly 12 is encapsulated in the housing cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the lithium-ion battery 1 can be one or more, which can be adjusted according to demand.
[0142] In some embodiments, secondary batteries may be assembled into a battery module. The battery module may contain multiple secondary batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0143] In the battery module, the plurality of secondary batteries may be arranged in sequence along the length direction of the battery module. Of course, they may also be arranged in any other manner. Further, the plurality of lithium-ion batteries may be fixed by fasteners.
[0144] Optionally, the battery module may further include a housing having an accommodation space, and the plurality of secondary batteries are accommodated in the accommodation space.
[0145] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0146] The battery pack may include a battery box and a plurality of battery modules disposed in the battery box. The battery box includes an upper box body and a lower box body, and the upper box body can be covered on the lower box body to form a closed space for accommodating the battery modules. The plurality of battery modules can be arranged in the battery box in any manner.
[0147] Electrical devices
[0148] In a fourth aspect, the present application provides an electrical device, which includes at least one of the secondary battery, battery module or battery pack of the third aspect of the present application. The secondary battery, battery module or battery pack can be used as a power source for the device, or as an energy storage unit for the device. The device may be, but is not limited to, a mobile device, an electric vehicle, an electric train, a ship and a satellite, an energy storage system, etc.; wherein the mobile device may include, but is not limited to, at least one of a mobile phone, a laptop computer, etc.; the electric vehicle may include, but is not limited to, at least one of a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.
[0149] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0150] Figure 3 The power consumption device 2 is taken as an example. The power consumption device 2 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the high power and high energy density requirements of the device for the secondary battery, a battery pack or a battery module can be used.
[0151] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion battery may be used as a power source.
[0152] The beneficial effects of the present application are further illustrated below in conjunction with embodiments.
[0153] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the following will be further described in detail with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work belong to the scope of protection of the present application.
[0154] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0155] 1. Preparation of positive electrode materials
[0156] Example 1
[0157] The ternary material (as the core) was dispersed in anhydrous ethanol, and (NH4)F (as the precursor containing the X element) was slowly added. During the addition of (NH4)F, the solution was placed in a 60°C water bath and slowly stirred for 30 minutes. The structural formula of the ternary material is Li(Ni 92 The molar ratio of F contained in Co6Mn2)O2, (NH4)F to the residual lithium element on the surface of the ternary material is 1.5:1;
[0158] Slowly add Fe(NO3)3 (as a precursor containing the Z element) to the mixed solution after the above reaction, and place the solution in a 60°C water bath during the addition of Fe(NO3)3. After the addition is completed, slowly stir for 30 minutes; wherein the molar ratio of Fe contained in Fe(NO3)3 to the residual lithium element on the surface of the ternary material is 1.5:1;
[0159] The reaction liquid after the above reaction was filtered, and the filter residue was dried. The filter residue was heated at 350° C. for 4 h in an argon atmosphere to obtain a positive electrode material.
[0160] Example 2-17
[0161] The preparation method of the positive electrode material in Examples 2-17 is basically similar to the preparation method of the positive electrode material in Example 1, with the main difference being that at least one of the structural formula of the core, the type and / or amount of the precursor containing the X element, the type and / or amount of the precursor containing the Z element, the reaction temperature and / or time, and the heating treatment temperature and / or time is different.
[0162] The following items were measured for the positive electrode materials prepared in the above embodiments and comparative examples: the mass percentage of lithium element contained in the first coating layer in the positive electrode material, the thickness of the first coating layer, the mass percentage of Z element contained in the second coating layer in the positive electrode material, and the thickness of the second coating layer.
[0163] Comparative Example 1
[0164] The difference between Comparative Example 1 and Example 1 is that neither the first coating layer nor the second coating layer is prepared.
[0165] Comparative Example 2
[0166] The difference between Comparative Example 2 and Example 1 is that only the first coating layer is prepared, and the second coating layer is not prepared.
[0167] Comparative Example 3
[0168] The difference between Comparative Example 3 and Example 1 is that when preparing the first coating layer, the Al2O3 coating layer is prepared by co-deposition method, and the second coating layer is not prepared; the specific preparation process is as follows:
[0169] Add Al(NO3)·9H2O to an alcohol-water solution with a volume ratio of 1:1, stir until dissolved, add the ternary material (as the core), stir thoroughly to obtain a suspension. Adjust the pH of the suspension to 5 with ammonia water, stir for 30 minutes, let it stand, filter, dry, and calcine (400°C) to form an Al2O3 coating on the surface of the ternary material.
[0170] Comparative Example 4
[0171] The difference between Comparative Example 4 and Example 1 is that when preparing the second coating layer, the Al2O3 coating layer is prepared by coprecipitation method; the specific preparation process is as follows: the suspension after the first reaction is filtered to obtain powder particles containing the first coating layer; Al(NO3)·9H2O is added to an alcohol aqueous solution with a volume ratio of 1:1, stirred until dissolved, and the above powder particles are added, and stirred thoroughly to obtain a suspension. The pH of the suspension is adjusted to 5 with ammonia water, stirred for 30 minutes, and after standing, after suction filtration, drying, and roasting (400°C), an Al2O3 coating layer is formed on the surface of the powder particles containing the first coating layer.
[0172] Comparative Example 5
[0173] The difference between Comparative Example 5 and Example 1 is that the molar ratio of the X element in the precursor containing the X element to the lithium element remaining on the surface of the core is different, and the others are the same, as shown in Table 1. The parameter settings of the above-mentioned embodiments and comparative examples are shown in Table 1.
[0174] Table 1
[0175]
[0176] Among them, in Table 1, n1 represents the molar ratio of the X element in the precursor containing the X element to the lithium element remaining on the surface of the core, n2 represents the molar ratio of the Z element in the precursor containing the Z element to the lithium element remaining on the surface of the core; T2 represents the reaction temperature of the first reaction, T2 represents the reaction temperature of the second reaction, and T3 represents the temperature of the heating treatment; w1 represents the mass percentage of the lithium element contained in the first coating layer to the positive electrode material, and w2 represents the mass percentage of the Z element contained in the second coating layer to the positive electrode material; L1 represents the thickness of the first coating layer, and L2 represents the thickness of the second coating layer; LiX represents a salt containing both lithium and X elements, and ZX represents a salt containing both Z and X elements.
[0177] In Table 1, the mass percentage of the Z element contained in the second coating layer of the positive electrode material, the thickness of the second coating layer, and the salt containing both the Z element and the X element in the second coating layer in Comparative Example 5 were not detected, indicating that the second coating layer could not be formed; (NH4)F was completely used in the first reaction to react with the lithium element remaining on the surface of the inner core.
[0178] In Table 1, “~” means approximately; for example, “~2” in Comparative Example 5 means that the thickness of the first coating layer is approximately 2 nm.
[0179] It should be noted that the mass percentage of lithium contained in the first coating layer mentioned above in the positive electrode material is determined by the following method: the type and content of the X element and the Z element contained in the coating layer are determined by ion chromatography, and the portion of the X element used to form a compound with the Z element is deducted, and the remaining portion X is used to form the first coating layer together with the lithium element. The mass of the lithium element contained in the first coating layer can be inferred based on the mass of the remaining portion of the X element, and then the mass percentage of the lithium element contained in the first coating layer in the positive electrode material is calculated.
[0180] The thickness of the first coating layer mentioned above is measured by the following method: a transmission electron microscope is used to perform phase analysis on the surface of the positive electrode material, and the thickness information of the first coating layer is obtained simultaneously.
[0181] The mass percentage of the Z element contained in the second coating layer mentioned above in the positive electrode material is determined by the following method: the types and contents of the X element and the Z element contained in the coating layer are determined by ion chromatography, and the mass percentage of the Z element in the positive electrode material is further calculated.
[0182] The thickness of the second coating layer mentioned above is measured by the following method: a transmission electron microscope is used to perform phase analysis on the surface of the positive electrode material, and the thickness information of the second coating layer is simultaneously obtained.
[0183] In Example 6, the molar ratio of the X element in the precursor containing the X element to the residual lithium element on the surface of the core is as high as 7:1, the thickness of the second coating layer is as high as 13nm, and the mass percentage of the Z element contained in the second coating layer is as high as 0.92% of the positive electrode material; the technicians analyzed that the reason may be that: the precursor containing the X element is added in excess, and after the residual lithium and the precursor containing the X element form the first coating layer, there may still be too much precursor containing the X element remaining, and the precursor containing the X element and the precursor containing the Z element continue to react to form the second coating layer, and the thickness of the formed second coating layer is too large.
[0184] In Example 10, the molar ratio of the X element in the precursor containing the X element to the lithium element remaining on the surface of the core is 1.5:1, and the molar ratio of the Z element in the precursor containing the Z element to the lithium element remaining on the surface of the core is 0.125:1. The mass percentage of the Z element contained in the second coating layer in the positive electrode material is only about 0.11%; the technicians analyzed that the reason may be that: the amount of X element added to the precursor containing the X element and the amount of the element-containing precursor added are both small, resulting in too low a generation amount of the second coating layer, and the mass percentage of the Z element contained in the second coating layer in the positive electrode material is also reduced.
[0185] The thickness of the first coating layer in Example 17 is as high as 10 nm, and the lithium element contained in the first coating layer accounts for 0.25% by mass of the positive electrode material, indicating that the residual lithium content on the surface of the core in Example 17 is relatively high.
[0186] 2. Preparation of secondary batteries
[0187] 1. The positive electrode material, acetylene black (as a conductive agent), and polyvinylidene fluoride (as a binder) are dissolved in N-methylpyrrolidone (as a solvent) at a weight ratio of 96.5:1.5:2, and the mixture is stirred and mixed to obtain a positive electrode slurry; the positive electrode slurry is then evenly coated on both sides of the aluminum foil, dried, cold pressed, and cut to obtain a positive electrode sheet.
[0188] 2. The negative electrode active materials graphite, acetylene black (as a conductive agent), sodium carboxymethyl cellulose (as a thickener), and styrene-butadiene rubber (as a binder) are dissolved in deionized water (as a solvent) in a weight ratio of 95:1:2:1, and the mixture is stirred and mixed to obtain a negative electrode slurry; the negative electrode slurry is then evenly coated on both sides of the copper foil, dried, cold pressed, and cut to obtain a negative electrode sheet.
[0189] 3. Use PE film as diaphragm.
[0190] 4. Preparation of Electrolyte
[0191] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte. In the electrolyte, the concentration of LiPF6 is 1 mol / L.
[0192] 5. Stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, then wind to obtain a bare cell, weld the tabs to the bare cell, and put the bare cell into an aluminum shell, bake at 80°C to remove water, then inject electrolyte and seal to obtain an uncharged battery. The uncharged battery then goes through the processes of static, hot and cold pressing, formation, shaping, capacity testing, etc. to obtain a secondary battery.
[0193] 3. Secondary battery performance test
[0194] 1. Cycle life test
[0195] At 25°C, charge the battery to 80% SOC at a constant current of 0.5C, and then charge it to 4.25V at a constant current and voltage of 0.33C. After standing for 5 minutes, discharge the battery to 2.8V at a constant current of 0.5C to complete a charge and discharge cycle. Record the number of cycles when the battery capacity decays to 80% SOC.
[0196] 2. High temperature flatulence test
[0197] Weld gas-generating pins at the battery cell injection sealing pins, and connect the pressure gauge through the oil pipe. Perform a cycle test according to the above cycle life test process at 45°C, and monitor the pressure increase simultaneously. The number of cycles when the pressure reaches 0.35Mpa is used as the inflation evaluation parameter.
[0198] The performance test structures of the above embodiments and comparative examples are shown in Table 2.
[0199] Table 2
[0200]
[0201]
[0202] Here, "~" means approximately. For example, the cycle life result "~3500" in Example 1 means approximately 3500 cycles.
[0203] It can be seen from the results of Examples 1-17 and Comparative Examples 1-5 that the positive electrode material provided in the present application can improve the cycle life and safety of the secondary battery.
[0204] The difference between Examples 1-6 and Comparative Example 5 is mainly that the molar ratio of the X element in the precursor containing the X element to the residual lithium element on the surface of the core and the molar ratio of the Z element in the precursor containing the Z element to the residual lithium element on the surface of the core are different; in Example 6, the molar ratio of the X element in the precursor containing the X element to the residual lithium element on the surface of the core and the molar ratio of the Z element in the precursor containing the Z element to the residual lithium element on the surface of the core are the largest, and the molar ratio of the X element in the precursor containing the X element to the residual lithium element on the surface of the core and the molar ratio of the Z element in the precursor containing the Z element to the residual lithium element on the surface of the core are the smallest in Comparative Example 5; It can be seen from the results of Examples 1-6 and Comparative Example 5 that when the molar ratio of the X element in the precursor containing the X element to the residual lithium element on the surface of the core is (1.5-6):1 and the molar ratio of the Z element in the precursor containing the Z element to the residual lithium element on the surface of the core is (0.125-2.5):1, the prepared positive electrode material can improve the cycle life and safety of the secondary battery.
[0205] Moreover, when the molar ratio of the X element in the precursor containing the X element to the residual lithium element on the surface of the core is lower than 3:1, the residual lithium consumption is small, the thickness of the first coating layer is small, and the high-temperature flatulence test result is poor; at the same time, due to the small amount of the precursor containing the X element added, the coating amount of the second coating layer will also be small, affecting the cycle effect. When the molar ratio of the X element in the precursor containing the X element to the residual lithium element on the surface of the core is higher than 3:1, the residual lithium on the surface of the core is completely consumed, but the overall coating amount increases, which will lead to an increase in the surface impedance of the positive electrode material and an increase in polarization, which is not conducive to improving the life.
[0206] In Example 6, the molar ratio of the X element in the precursor containing the X element to the residual lithium element on the surface of the core is as high as 7:1, and the molar ratio of the Z element in the precursor containing the Z element to the residual lithium element on the surface of the core is as high as 2:1. Examples 1-5 are better than Example 6 in terms of cycle performance, and Examples 2-6 are better than Example 6 in terms of high-temperature swelling results. The technicians analyzed that the reason may be that: in Example 6, the residual lithium on the surface of the core can be completely consumed, but due to the introduction of too much X element, the second layer coating may be too thick, which may affect the long-term performance.
[0207] The main difference between Example 3 and Example 17 is that the thickness of the first coating layer is different; Example 3 is better than Example 17 in both cycle performance and safety; technicians analyzed that the reason may be that: the residual lithium content on the surface of the inner core in Example 17 may be higher, resulting in a higher thickness of the first coating layer, which may deteriorate the performance of the positive electrode material itself.
[0208] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0209] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A positive electrode material, characterized in that: include: A core, wherein the material of the core comprises a lithium nickel cobalt metal composite oxide; in the lithium nickel cobalt metal composite oxide, the molar proportion of nickel element in the total metal elements other than lithium element is 30%-95%; A first coating layer, coated on at least a portion of the outer surface of the core, wherein the material of the first coating layer includes lithium and X elements; and A second coating layer, coating at least a portion of the outer surface of the core having the first coating layer, wherein the material of the second coating layer includes an X element and a Z element; The X element includes one or more of fluorine, chlorine and bromine, and the Z element includes one or more of iron, titanium, aluminum, zinc and magnesium.
2. The positive electrode material according to claim 1, characterized in that The second coating layer is coated on the entire outer surface of the inner core having the first coating layer.
3. The positive electrode material according to claim 1, characterized in that The structural formula of the lithium nickel cobalt metal composite oxide is Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y , wherein 0.2≤x≤1.2, a+b+c=1, the M element includes one or more of Al, Mg, Zr, W, Ti and Y, and the A element includes one or more of B, P and F.
4. The positive electrode material according to any one of claims 1 to 3, characterized in that The first coating layer has at least one of the following characteristics: (1) The mass percentage of the lithium element contained in the first coating layer to the positive electrode material is 0.1%-0.3%; (2) The material of the first coating layer includes a salt containing both the lithium element and the X element; (3) The thickness of the first coating layer is 3nm-10nm.
5. The positive electrode material according to any one of claims 1 to 3, characterized in that The second coating layer has at least one of the following characteristics: (1) The mass percentage of the Z element contained in the second coating layer to the positive electrode material is 0.2%-0.6%; (2) the material of the second coating layer includes a salt containing both the Z element and the X element; (3) The thickness of the second coating layer is 5nm-10nm.
6. A method for preparing a positive electrode material according to any one of claims 1 to 5, characterized in that: The steps include: Dispersing the core in a solvent, adding a precursor containing the element X at 40° C. to 70° C., and performing a first reaction to prepare the first coating layer on at least a portion of the surface of the core; A precursor containing the Z element is added to the reaction solution of the first reaction at 40° C.-70° C. to carry out a second reaction, so as to prepare the second coating layer on at least a portion of the surface of the core having the first coating layer.
7. The method for preparing the positive electrode material according to claim 6, characterized in that: The first reaction comprises at least one of the following conditions: (1) The precursor containing the element X includes an acidic salt containing the element X; Optionally, the precursor containing element X includes one or more of ammonium fluoride, ammonium chloride and ammonium bromide; (2) The molar ratio of the X element contained in the X element precursor to the lithium element remaining on the surface of the core is (1.5-6):1; optionally (2-4):1; more preferably 3:1; (3) After adding the precursor containing the element X, the reaction time is 20 min to 40 min; (4) The solvent includes a fatty alcohol; Optionally, the solvent includes one or more of ethanol, ethylene glycol, propanol, butanol and butanediol.
8. The method for preparing a positive electrode material according to any one of claims 6 to 7, characterized in that: The second reaction comprises at least one of the following conditions: (1) The Z-containing precursor includes one or more of nitrates, carbonates, sulfates and sulfites containing the Z element; the Z element includes one or more of iron, titanium, aluminum, zinc and magnesium; (2) The molar ratio of the Z element contained in the Z element-containing precursor to the lithium element remaining on the surface of the core is (0.125-2.5):1; can be (0.25-1.5):1; more preferably 0.66:1; (3) After adding the Z-containing precursor, the reaction time is 20 min to 40 min.
9. The method for preparing a positive electrode material according to any one of claims 6 to 8, characterized in that: The following steps are also included: The reaction liquid obtained by the second reaction is filtered, the filter residue is dried, and the filter residue is subjected to a heat treatment under a protective atmosphere to prepare the positive electrode material.
10. The method for preparing the positive electrode material according to claim 9, characterized in that: The heat treatment includes at least one of the following conditions: (1) The protective gas used includes one or more of nitrogen and inert gas; Optionally, the protective gas used includes one or more of nitrogen and argon; (2) The reaction temperature is 300°C-400°C and the reaction time is 3h-5h.
11. A positive electrode sheet, characterized in that: include: Positive electrode current collector; and A positive electrode active material layer is located on at least one side of the positive electrode current collector, and the positive electrode active material layer comprises the positive electrode material according to any one of claims 1 to 5.
12. A secondary battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 11.
13. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 12.
Citation Information
Patent Citations
Cathode active material, cathode, and non-aqueous electrolyte secondary battery
CN101414680A
Lithium ion secondary battery cathode material and preparation method thereof
CN112490444A
Positive electrode material, preparation method thereof and battery
CN113346069A
Cathode material with low residual alkali content and preparation method and application thereof
CN115172713A
Lithium cobalt oxide positive electrode material, electrochemical device, electronic apparatus, and mobile device
CN115706222A
Cited By
Positive electrode material, preparation method and device thereof and lithium ion battery
CN119400845A
A positive electrode material and preparation method, device and lithium ion battery
CN119400845B
Positive electrode material, preparation method and battery
CN120072886A
